The Origin and Practice of Federalism of Federalism in Nigeria (Journal of Governance and Development (JGD), 2016)
Federalism is a political philosophy meant to ‘integrate people in a society who are diverse ethnically, culturally and even religiously’. The system in Nigeria is not without complexities and problems. The federal system is a mechanism for solving the burning question of public power domination by a certain group in a multi-cultural society. Therefore, this paper attempts an assessment of the practice of Nigerian federalism. To achieve this, the paper considered the pluralist nature of Nigeria as a framework for analysis and relies essentially on qualitative data. The theory focuses on the diversity of competing group and the commitment to the principles among the group leaders. Since it is fundamental that the challenges of fiscal federalism, federal character, nation building and minority interest are enormous that negates the basic principles of system Nigerian, the paper concludes by arguing that there is a prospect of a stable federal system if anchored on arrangement rooted in equity, fairness and justice among the various nationalities in the polity.